Il mostruoso femminino in Tanz e A Divine Comedy di Florentina Holzinger - Trachsel, Ekaterina (Kritik. Rivista di letteratura e critica culturale, 2024)
This paper is concerned with Florentina Holtzinger’s dramatization of Anita Berber and Sebastian Droste’s 1922 dances of vice, horror, and ecstasy [Tänze des Lasters, des Grauens und der Ekstase]. In her performances, the structural convention of the three-act ballet and the historical legacy of images and movements is alienated, contemporary equivalents are sought for productions historically received as scandalous, and the monstrous montage of their work is explicitly revealed. This method plays with the breaking of taboos and draws attention to the norms and mechanisms of censorship.